The interplay of TARG1 and PARG protects against genomic instability - Joséphine Groslambert; Evgeniia Prokhorova; Anne R. Wondisford; Callum Tromans-Coia; Celeste Giansanti; Jennifer Jansen; Gyula Timinszky; Matthias Dobbelstein; Dragana Ahel; Roderick J. O’Sullivan; Ivan Ahel (Cell Reports, 2023)
Summary: The timely removal of ADP-ribosylation is crucial for efficient DNA repair. However, much remains to be discovered about ADP-ribosylhydrolases. Here, we characterize the physiological role of TARG1, an ADP-ribosylhydrolase that removes aspartate/glutamate-linked ADP-ribosylation. We reveal its function in the DNA damage response and show that the loss of TARG1 sensitizes cells to inhibitors of topoisomerase II, ATR, and PARP. Furthermore, we find a PARP1-mediated synthetic lethal interaction between TARG1 and PARG, driven by the toxic accumulation of ADP-ribosylation, that induces replication stress and genomic instability. Finally, we show that histone PARylation factor 1 (HPF1) deficiency exacerbates the toxicity and genomic instability induced by excessive ADP-ribosylation, suggesting a close crosstalk between components of the serine- and aspartate/glutamate-linked ADP-ribosylation pathways. Altogether, our data identify TARG1 as a potential biomarker for the response of cancer cells to PARP and PARG inhibition and establish that the interplay of TARG1 and PARG protects cells against genomic instability.